Studi Retrospektif Profil Kliniko-Patologi Kanker Serviks di RSUD Saiful Anwar Malang Periode 2022–2024 - Ulfatun Nahdhiyah; Hendy Setyo Yudhanto; Arif Satria Hardika (RSUD Dr. Saiful Anwar Province of East Java, 2026)
Background: Cervical cancer is one of the leading causes of morbidity and mortality in women worldwide, especially in developing countries including Indonesia. Oncogenic Human Papillomavirus (HPV) infection is the main etiologic factor, with limited access to screening and vaccination as a major obstacle to prevention and early detection. Epidemiologic data and clinicopathologic profiles of cervical cancer are essential for understanding disease trends and improving prevention and management strategies. Aim: This study aims to determine the frequency distribution of cervical cancer based on year of diagnosis, age, and histopathology type at the Anatomical Pathology Laboratory of Saiful Anwar Hospital Malang from January 2022 to December 2024. Methods: This study used a retrospective descriptive design by analyzing secondary data from the medical records of the Anatomical Pathology Laboratory of Saiful Anwar Hospital Malang. The study sample included all cases of cervical cancer confirmed through histopathologic examination within the study period. Results: From the analyzed data, 260 cases of cervical cancer were found and the distribution of cases increased every year. Most patients were diagnosed at the age of 51-60 years, with the most histopathological type being squamous cell carcinoma (SCC), followed by adenocarcinoma. Conclusion: This study provides an overview of the clinicopathologic profile of cervical cancer that can be the basis for improving cervical cancer screening, prevention, and management strategies in Indonesia, especially at Saiful Anwar Hospital Malang.